Measurement of Nitrogen Utilization Efficiency in Rice Genotypes - Broadbent, F.E.; De Datta, S.K.; Laureles, E.V. (Wiley, 1987)
Recent research suggests that there is considerable potential for exploiting genotypic differences in N utilization efficiency by crops. Our research attempted to identify traits associated with rice (Oryza sativa L.) genotypes that support maximum grain production with a minimum input of fertilizer. From field experiments on an Andaqueptic Haplaquoll in three consecutive seasons we identified a group of plant parameters associated with efficiency of N utilization to determine if the different genotypes exhibited consistent and significant variations in these parameters. A group of nine parameters was selected, and rankings based upon different combinations of these parameters were developed and compared. Statistically significant differences among genotypes were observed, and reasonably consistent rankings were obtained from season to season. For example, IR183429‐3‐2‐1‐2 ranked first in two seasons and third in the other. IR18349‐135‐2‐3‐2‐1 ranked second, third, and fifth in the three seasons. These are medium maturity rices. IR42, which is known to perform well on low N soils, ranked between ninth and 17th. The consistency of performance of outstanding genotypes demonstrated in these experiments suggests that the methodology is feasible and practical for use in research on genetic improvement of N utilization efficiency.